Gravitational Acceleration: Its Determination from Gourami Jumping Motion Using Tracker Application - Ilma, Arina Zaida; Kuswanto, Heru (Pendidikan Fisika FITK UIN Sunan Kalijaga, 2024)
Jumping out of the water is one of the phenomena of aquatic animals. Analyzing the motions and routines of aquatic animals is a time-consuming process and tends to be subjective, prone to errors due to observer fatigue. In investigating the motion of objects is a difficult thought, but with the development of technology it becomes easy, one of them is by using the Tracker. This research aims to analyze the Gourami jumping motion using the Tracker in independent experiment activities about animal motion. The materials and tools needed include Gourami fish, Android camera, and Tracker application. The measurement results are the data on time, position, and the graph of motion. Gourami jumping motion is a parabolic motion consisting of uniform linear motion on the x-axis, while uniformly accelerated linear motion on the y-axis. The value of the gravitational acceleration can be determined from the graph and its value is close to the gravitational acceleration constant. The use of video analysis of the Gourami motion using the Tracker can be used in science learning, especially in physics experiment.